Caesalpinia bonducella seeds restore the ovarian functions in mifepristone-induced PCOS rats acting through insulin –insulin-like growth factors (Indian Journal of Traditional Knowledge (IJTK), 2024)
The prime complications namely hyperandrogenism and hyperinsulinemia, observed in PCOS condition is due to the abnormal signalling pathways triggered by insulin as well as insulin-like growth factor family of genes and proteins. The aim of the present study is to evaluate the down regulating effect of ethanolic seed extract of Caesalpinia bonducella (ESECB) on the genes like IGF-1, IGF-2 and PTEN and proteins IRS1 and IRS2 in mifepristone induced PCOS rats. The level expression pattern of genes were studied using in vivo methods and the in silico method is used to study the proteins. Mifepristone induced PCOS rats were treated with 200 mg and 400 mg/kg b.w. p.o of ESECB extract for 28 days. The ovaries were collected for gene expression study using semi quantitative real time PCR analysis. Molecular docking analysis was performed from the GC-MS phyto-constituents for a antagonistic ligand which can halt the reactions of IRS1 and IRS2 proteins. The fold change of the mRNA expression of IGF-1, IGF-2 and PTEN genes were found to be 1.4, 0.34 and 0.36 respectively in the mifepristone induced PCOS rat ovaries. ESECB treatment decreased the fold change to 0.44, 0.13 and 0, 20 respectively. In docking studies, eight ligands namely, dioxan, propyl acetate, acetic anhydride, methyl butenoic acid, methyl isopropyl carbonate, glycerine, diethanolamine and 2,2, dimethyl propanoic anhydride inhibted the IRS1 and IRS2 proteins by interacting with their amino acid residues. It can be concluded that ESECB extract can be used as a potential drug for the treatment of PCOS as it acts at the molecular level to correct the complications of this disease.